Complete genome sequence of Acidihalobacter prosperus strain F5, an extremely acidophilic, iron- and sulfur-oxidizing halophile with potential industrial applicability in saline water bioleaching of chalcopyrite - Khaleque, H.; Corbett, M.; Ramsay, Joshua; Kaksonen, A.; Boxall, N.; Watkin, E. (Elsevier Science, 2017)
© 2017 Successful process development for the bioleaching of mineral ores, particularly the refractory copper sulfide ore chalcopyrite, remains a challenge in regions where freshwater is scarce and source water contains high concentrations of chloride ion. In this study, a pure isolate of Acidihalobacter prosperus strain F5 was characterized for its ability to leach base metals from sulfide ores (pyrite, chalcopyrite and pentlandite) at increasing chloride ion concentrations. F5 successfully released base metals from ores including pyrite and pentlandite at up to 30 g L -1 chloride ion and chalcopyrite up to 18 g L -1 chloride ion. In order to understand the genetic mechanisms of tolerance to high acid, saline and heavy metal stress the genome of F5 was sequenced and analysed. As well as being the first strain of Ac. prosperus to be isolated from Australia it is also the first complete genome of the Ac. prosperus species to be sequenced. The F5 genome contains genes involved in the biosynthesis of compatible solutes and genes encoding monovalent cation/proton antiporters and heavy metal transporters which could explain its abilities to tolerate high salinity, acidity and heavy metal stress. Genome analysis also confirmed the presence of genes involved in copper tolerance. The study demonstrates the potential biotechnological applicability of Ac. prosperus strain F5 for saline water bioleaching of mineral ores.